Multi‐residue analysis of 206 pesticides in grass forage by the one‐step quick, easy, cheap, effective, rugged, and safe method combined with ultrahigh‐performance liquid chromatography quadrupole orbitrap mass spectrometry. Issue 14 (21st May 2022) - Wu, Xingqiang; Li, Tiemei; Feng, Hailing; Xie, Yujie; Liu, Fangyu; Tong, Kaixuan; Fan, Chunlin; Liu, Yingtao; Chen, Hui
Abstract : A novel method for detecting pesticide multi‐residue in grass forage (alfalfa and oat) was established based on the one‐step automatic extraction and purification technology of quick, easy, cheap, effective, rugged, and safe combined with ultrahigh‐performance liquid chromatography quadrupole Orbitrap high‐resolution mass spectrometry. The crushed sample was extracted with acetonitrile with 1% acetate, followed by a cleanup step with a primary‐secondary amine, octadecylsilane, and graphitized carbon black. The extraction and purification were carried out using the one‐step automatic pretreatment equipment. The target pesticides were acquired in positive ion electrospray ionization mode and full scan/data dependent secondary scan mode. The calibration curve shows good linearity over the corresponding concentration range, with the coefficient of determination greater than 0.99. The screening detection limits were 0.5–50 μg/kg, and the limit of quantification for the 206 pesticides was set at 1–50 μg/kg. At the spiking levels of one, two, and 10 times of limit of quantification, more than 95% of pesticides had recovery between 70–120%, with a relative standard deviation ≤20%. The method was proved to be simple, rapid, high‐sensitivity, and could be routinely used for the high throughput screening and quantitative analysis of pesticide residues in alfalfa and oat.